The Election Violations Conducted by Election Organizers of Aceh Besar Regency - Taqdirullah Taqdirullah; Syarifuddin Hasyim; M. Adli (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
This research aims to analyze election violations committed by election organizers in Aceh Besar Regency in 2019. The violation of this election occurred at several points in the sub-district of aceh regency, where the violation of the law is contained in the administration of the election file and also in the part of the organizer that is the election implementation team. This is one of the indicators in this study. Using empirical juridical research methods and qualitative data analysis, the study found that there were only 5 (five) unlawful actions in aceh besar district elections, among which there were un registerable reports, muted reports and follow-up reports to the Jantho District Court. It is recommended to the government, Bawaslu, Panwaslih to conduct more checking or control and also full supervision on a scale to minimize the on-the-process election violations in Aceh Besar Regency in particular as well as other districts.